ACCOUNTING SERVICES AND THE FINANCIAL PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN IKOT EKPENE METROPOLIS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The study examined the accounting services and the financial performance of small and medium enterprises in Ikot Ekpene metropolis. In order to carry out this study, specified research objectives were drawn from which null hypotheses were formulated and used for the study. The research design for this study is survey method design. The population of the study consisted of SMEs operators in Ikot Ekpene local government area. Simple random sampling technique was used to select 383 respondents out of the population. The instrument used for data collection was questionnaire. Data from completed questionnaires was subjected to regression analysis. The findings showed that findings showed that the current accounting practice has a significantly positive effect on SMEs performance. The positive correlation indicates that the higher the soundness of accounting practices deplored on the operations, the higher the performance of the business and vice versa. This is based on the premise that sound accounting practice will lead the firm to account accurately for all its incomes and expenditures as well as assets and liabilities from one period to the other.